Do Cultural Differences Matter in Mergers and Acquisitions? A Tentative Model and Examination - Stahl, Günter K.; Voigt, Andreas (Organization Science, 2008)
Asubstantive body of theory and research on the role of culture in mergers and acquisitions (M&A) suggests that cultural differences can create major obstacles to achieving integration benefits. However, the opposite view—that differences in culture between merging firms can be a source of value creation and learning—has also been advanced and empirically supported. In an attempt to reconcile these conflicting perspectives and findings, we present a model that synthesizes our current understanding of the role of culture in M&A, and we develop a set of hypotheses regarding mechanisms through which cultural differences affect M&A performance. The results of a meta-analysis of 46 studies, with a combined sample size of 10,710 M&A, suggest that cultural differences affect sociocultural integration, synergy realization, and shareholder value in different, and sometimes opposing, ways. Moderator analyses reveal that the effects of cultural differences vary depending on the degree of relatedness and the dimensions of cultural differences separating the merging firms, as well as on research design and sample characteristics. The implications for M&A research and practice are discussed.